PERAN BELAJAR BERDASAR REGULASI DIRI DAN PENYESUAIAN DIRI TERHADAP PRESTASI BELAJAR SISWI MADRASAH TSANAWIYAH MUALLIMAT YOGYAKARTA - Damayanti, Eka (Jurnal Biotek, 2015)
The purpose of this study is to determine the role of self-regulated learning and self-adjustment in learning achievement. The research subjects are consisted of 121 first grade students (ages 12-14 years) at one junior secondary schooling Yogyakarta. The research measurement scales are consisted of self-regulated learning and self-adjustment. The learning aachievement data are collected from the student card report. Â Data analysis was done by using multiple regression analysis with the help of SPSS computer program. The analysis result shows that self regulated learning and self adjustment jointly have a significant role on student achievement (F-value of 3.089 significance probability value of 0.049,p < 0.05) Based on the partial test, it can be seen that the self regulated learning variables and self-adjustment variables separately had no significant role of student achievement. It can be seen from the probability values of significance respectively of 0.496 (p > 0.05) and 0.072 (p > 0.05).